The role of schools in setting environmental awareness with students at basic teaching schools “A field study on a sample of teachers in the city of Lattakia ” - حيدر ربا (Latakia University Journal - Arts and Humanities Sciences Series, 2021)
This study aimed to recognize the role of schools in spreading environmental awareness in basic teaching schools from the point of view of class teachers in schools of Lattakia according to the variable of gender, academic qualification, and years of expertise. The study was performed on a random sample of 202 teachers in which a form of 302 parts was used. The study reached, through averages and standard deviations and percentage and significance level, to difference between the average of teachers with the role of school’s management in setting the environmental awareness according to variable of gender with priority to females and a difference with a statistic significance according to variable of years of expertise for those who have less than five years’ experience plus no difference with stastistice significance in the average of degrees of teachers in setting environmental awareness with teacher of basic teaching students according to the variable of academic qualification. It was shown that the role of schools in setting environmental awareness comes into the middle.